Evaluation of the Effect of Four Bioactive Compounds in Combination with Chemical Product against Two Spider Mites Tetranychus urticae and Eutetranychus orientalis(Acari: Tetranychidae). (22nd August 2022) - Assouguem, Amine; Kara, Mohammed; Ramzi, Amal; Annemer, Saoussan; Kowalczyk, Alicja; Ali, Essam A.; Moharram, Bushra Abdulkarim; Lazraq, Abderrahim; Farah, Abdellah
Abstract : Currently, pests control using chemical acaricides constitutes worries for ecologists and health care people as these chemical products create damage to the ecosystem as well as the development of spider mites resistance. Such concerns request deep and rapid feedback by looking for new alternative and eco-friendly methods. In recent years, a new field is evolving in the use of essential oils in pest management practices. Essential oils have been considered as potential pest management agents, because they demonstrate to have a broad range of bioactivity, possess contact, and fumigant toxicity. In addition, the major advantages of many plant-based acaricides lie in their low toxicity to agroecosystems. Botanical acaricides composed of essential oils may prove to be a good choice for the more persistent synthetic acaricides. In this study, the acaricidal effect of four plant-derived essential oils against adults of the two important crop pests, Tetranychus urticae (Koch) 1836 and Eutetranychus orientalis (Klein) 1936 are studied. The fumigant toxicity revealed that all the essential oils tested Mentha pulegium L., Lavandula stoechas L., Rosmarinus officinalis L., and Origanum compactum Benth (Lamiaceae family) displayed an acaricidal effect. At the highest dose (625 µl/ml), mortalities recorded were found between 91 and 98% and 92 and 99% at 24 and 48 h, respectively, for T. urticae, and between 90 and 98% and 94 and 99% at 24 and 48 h, respectively, for E. orientalis . The M. pulegium L. essential oil represents the highest activity against E. orientalis and T. urticae . For the binary combination between the EOs (essential oils) and the acaricide based on the active ingredient acequinocyl, the results showed that the mixture of O. compactum EO (essential oil) + acequinocyl exhibited an important acaricidal effect on T. urticae and E. orientalis with 99% at 24 h and 100% at 48 h of mortality, followed by M. pulegium EO + acequinocyl with 92% at 24 h and 95% at 48 h for T. urticae as well as 99% at 24 h and 100% at 48 h for E. orientalis of mortality. Whereas, the mixture of L. stoechas EO + acequinocyl presented the lowest activity against T. urticae and E. orientalis with 82–87% at 24 h and 86–90% at 48 h, respectively . The mixtures ( M. pulegium EO + acequinocyl, R. officinalis EO + acequinocyl, and O. compactum EO + acequinocyl) exerted a high acaricidal effect against E. orientalis . These promising results could help to develop botanical pesticides that could be used in integrated pest management.